Requirements concerning the evolution of the Utilaje Park in Romania in period 2012-2018 - Maria Cristina Sterie (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The machinery fleet is of particular importance for Romania's agriculture because it helps to preserve comfort, sustainability of agricultural production and the replacement of human energy. In Romania the machines illustrate a positive growth rate, the mechanization being favoured by non-refundable funding. Submeasure 4.1. Investments in agricultural holdings stimulate the purchase of agricultural machinery, the results can be observed in the long term, based on the environmental benefits, yields and quality of agricultural products.
Keywords: Q10; 330; agriculture; machinery park; non-refundable financing